Commensal and Pathogenic Bacterial-Derived Extracellular Vesicles in Host-Bacterial and Interbacterial Dialogues: Two Sides of the Same Coin. (17th February 2022) - Tarashi, Samira; Zamani, Mohammad Saber; Omrani, Mir Davood; Fateh, Abolfazl; Moshiri, Arfa; Saedisomeolia, Ahmad; Siadat, Seyed Davar; Kubow, Stan
Abstract : Extracellular vesicles (EVs) cause effective changes in various domains of life. These bioactive structures are essential to the bidirectional organ communication. Recently, increasing research attention has been paid to EVs derived from commensal and pathogenic bacteria in their potential role to affect human disease risk for cancers and a variety of metabolic, gastrointestinal, psychiatric, and mental disorders. The present review presents an overview of both the protective and harmful roles of commensal and pathogenic bacteria-derived EVs in host-bacterial and interbacterial interactions. Bacterial EVs could impact upon human health by regulating microbiota–host crosstalk intestinal homeostasis, even in distal organs. The importance of vesicles derived from bacteria has been also evaluated regarding epigenetic modifications and applications. Generally, the evaluation of bacterial EVs is important towards finding efficient strategies for the prevention and treatment of various human diseases and maintaining metabolic homeostasis.